(untitled) (Itinera, 2025)
Mould plays music. Sound, nature and technology This article investigates the role of sound as a tool to rethink the relationship between nature, culture, and technology, questioning the modern dichotomy that separates them. Building on R. Murray Schafer’s reflections on soundscape and Steven Feld’s acoustemological approach, sound is understood as an ecological and multispecies form of knowledge, capable of establishing connections between human and non-human agents. Within this framework, artistic practices of sonification are examined as ways of making otherwise invisible biological phenomena audible, transforming data and vital signals into both aesthetic and epistemic experiences. The case study of artist and researcher Eduardo Reck Miranda, who experiments with the slime mold Physarum polycephalum in dialogue with artificial intelligence systems, demonstrates how living organisms can become compostional agents within a sonic interaction with humans. Though biomemristors and the Phy-Box device, the slime mold becomes part of a hybrid musical system, opening a broader reflection on the possibility of post-anthropocentric music. What emerges is an ecology of listening, where sound functions as an epistemic, relational, and intermedial practice, enhancing our coexistence with the natural world.